Post-disaster tourism governance; public perceptions of disaster mitigation and tourism safety post-tsunami in Tanjung Lesung, Indonesia - Berthanila, Rethorika; Maulana, Delly; Ema Jumiati, Ipah (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
Tanjung Lesung, as a tourism Special Economic Zone (SEZ), faces significant challenges in restoring its tourism image after the disaster. Therefore, understanding public perceptions of mitigation efforts and traveller safety is critical in determining the effectiveness of destination recovery strategies. This study aims to analyse the influence of disaster mitigation, tourism security, satisfaction with sustainable tourism policies, and post-disaster psychological conditions on public perceptions of Tanjung Lesung after the tsunami. This study uses a quantitative approach with a survey method. Data was collected from 97 valid respondents and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with Smart PLS4 software. The results show that disaster mitigation and tourism security have a significant influence on community perceptions of tourist destinations. In addition, satisfaction with sustainable tourism policies acts as a mediator in the relationship between disaster mitigation and community perceptions. Other findings revealed that post-disaster psychological conditions have a significant impact on community satisfaction with tourism policies and their perceptions of tourist destination security. Based on the results of this study, an integrated approach that includes comprehensive disaster mitigation policies, improved tourism security, and attention to the psychological state of the community is needed to rebuild community trust in post-disaster tourist destinations. This study provides important insights for policy makers and destination managers in designing more effective recovery strategies to ensure the sustainability of the tourism sector in disaster-affected areas.